2011
DOI: 10.1182/blood-2010-12-323212
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of target genes regulated by HoxB4 in hematopoietic stem and progenitor cells developing from embryonic stem cells

Abstract: Forced expression of the transcription factor HoxB4 has been shown to enhance the self-renewal capacity of mouse bone marrow hematopoietic stem cells (HSCs) and confer a long-term repopulating capacity to yolk sac and embryonic stem (ES) cell-derived hematopoietic precursors. The fact that ES cell-derived precursors do not repopulate bone marrow without HoxB4 underscores an important role for HoxB4 in the maturation of ES-derived hematopoietic precursors into long-term repopulating HSCs. However, the precise m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 34 publications
3
40
1
Order By: Relevance
“…19 Second, it has been suggested that HOXB4 induces stem cell expansion through c-myc expression, resulting in enhancement of HSC self-renewal. 20 In agreement, the study by Oshima et al 21 and ours showed that c-myc (and its partner max in our study) was up-regulated in HSC exposed to HOXB4 (or to HOXC4). Third, IGF-1 signaling is required for the maintenance or growth of various stem cells, particularly mesenchymal stem cells, 22 spermatogonia, 23 and hematopoietic stem and progenitors cells, and IGF-1 is involved in normal erythropoiesis, granulopoiesis, and lymphopoiesis.…”
Section: Hoxb4 and Hoxc4 Regulate Genes Important In Various Cell Grosupporting
confidence: 81%
See 1 more Smart Citation
“…19 Second, it has been suggested that HOXB4 induces stem cell expansion through c-myc expression, resulting in enhancement of HSC self-renewal. 20 In agreement, the study by Oshima et al 21 and ours showed that c-myc (and its partner max in our study) was up-regulated in HSC exposed to HOXB4 (or to HOXC4). Third, IGF-1 signaling is required for the maintenance or growth of various stem cells, particularly mesenchymal stem cells, 22 spermatogonia, 23 and hematopoietic stem and progenitors cells, and IGF-1 is involved in normal erythropoiesis, granulopoiesis, and lymphopoiesis.…”
Section: Hoxb4 and Hoxc4 Regulate Genes Important In Various Cell Grosupporting
confidence: 81%
“…Importantly, we noted that the modified expression of 33 genes in our study is shared by genes in the study by Oshima et al described as potential direct targets of HOXB4. 21 Gene expression variations reported in various publications often lead to divergent or contradictory results because the models used in the studies are different. Our model is the only one that takes into consideration the effects of HOXB4 and HOXC4 proteins on gene expression in human HSC.…”
Section: Hoxb4 and Hoxc4 Regulate Genes Important In Various Cell Gromentioning
confidence: 99%
“…Hoxb4 modulates HSC responsiveness to several extrinsic cues and displays a dose-dependent effect on HSC self-renewal, supporting normal differentiation versus perturbed differentiation (Klump et al, 2005;Schiedlmeier et al, 2007;Will et al, 2006). Context-specific HOXB4/Hoxb4 activity and promoter occupancy have been highlighted by genome-wide searches for targets, and these studies have revealed the dynamics of the Hoxb4 regulatory network in the embryonic stem to haematopoietic progenitor cell differentiation process (Fan et al, 2012;Oshima et al, 2011). Hoxb4 ChIP peaks correlate with known haematopoietic transcription factor binding sites or ChIP peaks, suggesting that Hoxb4 functions in a combinatorial fashion during haematopoiesis.…”
Section: The Functional Versatility Of Hox Proteinsmentioning
confidence: 99%
“…Very recently, a plausible mechanistic explanation has been offered for the inhibition of lymphopoiesis by HOXB4, based on the results of global gene expression comparisons and HOXB4 ChiP-Seq experiments [52]. In that study, five different HSPC types were compared: bone marrow HSCs, myeloid-biased and lymphoid-biased HSC subpopulations [53], HOXB4 ESC-HCs derived from our clone 8 (used in the present study), and independently established HOXB4 ESC-HCs [54]. Their results strongly suggest that HOXB4 ES-HSPCs are much more similar to the adult myeloid-biased (My-) HSC subtype than to lymphoidbiased HSCs.…”
Section: ␥Cmentioning
confidence: 99%